Jurisdictions and subordination changes in the administration of Rio Grande Captaincy: a survey on correspondences between colonial authorities (1695 - 1705) (Ágora Journal, 2021)
This article aims to analyze how the change on the subordination of the captaincy of Rio Grande in 1701 had its consequences over this captaincy territorialization process in a context of application of defense policies, return of sesmarias concessions on the hinterland and the actions of the officers of the Terço dos Paulistas. To this end, official documents from the local and royal administration, correspondence between the authorities will be analyzed. The theoretical contribution is based, mainly, on the concepts of jurisdiction, center and periphery, relevant to understand the process of the change on the subordination and the new jurisdictional configurations on the captaincy of Rio Grande henceforth annexed to Pernambuco’s captaincy. It will be considered the beginning of the government of capitão-mor Bernardo Vieira de Melo (1696) and the end of the mandate of his successor, Antonio de Carvalho e Almeida (1705), a period in which the administrative and greater intensity of correspondence is perceived when dealing with the matter among colonial authorities